Is there an agreement among the items of the Korean physical therapist licensing examination, learning objectives of class subjects, and physical therapists’ job descriptions? - Kang, Min-Hyeok (J Educ Eval Health Prof, 2016)
PURPOSE: To determine the agreement among the items of the Korean physical therapist licensing examination, learning objectives of class subjects, and physical therapists’ job descriptions. METHODS: The main tasks of physical therapists were classified, and university courses related to the main tasks were also classified. Frequency analysis was used to determine the proportions of credits for the classified courses out of the total credits of major subjects, exam items related to the classified courses out of the total number of exam items, and universities that offer courses related to the Korean physical therapist licensing examination among the surveyed universities. RESULTS: The proportions of credits for clinical decision making and physical therapy diagnosis-related courses out of the total number credits for major subjects at universities were relatively low (2.06% and 2.58%, respectively). Although the main tasks of physical therapists are related to diagnosis and evaluation, the proportion of physiotherapy intervention-related items (35%) was higher than that of examination and evaluation-related items (25%) on the Korean physical therapist licensing examination. The percentages of universities that offer physical therapy diagnosis and clinical decision making-related courses were 58.62% and 68.97%, respectively. CONCLUSION: Both the proportion of physiotherapy diagnosis and evaluation-related items on the Korean physical therapist licensing examination, and the number of subjects related to clinical decision making and physical therapy diagnosis in the physical therapy curriculum, should be increased to ensure that the examination items and physical therapy curriculum reflect the practical tasks of physical therapists.